No Uglies: Rejection and Utopia in "Animal Crossing: New Horizons" - Calloway, Alexander (Replay. The Polish Journal of Game Studies, 2024)
What motivates cruelty against video game characters designed to be friendly? Using human-to-NPC interactions within the game Animal Crossing: New Horizons as a case study, this paper seeks to define what aspects of a cozy game contribute towards public displays of aggression or kindness toward the game’s characters. An examination of public forums dedicated to discussing villagers deemed ugly reveals the importance of parasocial connections in the utopian community planning aspects of Animal Crossing’s gameplay. The resulting online discourse surrounding ethical treatment of villagers becomes part of players’ conceptions of their role as social planner in-game, further solidifying which behaviors and objectives will yield them the coziest experience. Paratext, therefore, plays an active role in the conception and socialization of Animal Crossing players’ utopian urban projects.